2011
DOI: 10.1111/j.1365-2133.2011.10643.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in leucocyte subsets and histomorphology in normal-appearing perilesional skin and early and chronic hidradenitis suppurativa lesions

Abstract: Psoriasiform hyperplasia, follicular plugging and low-grade leucocytic infiltration are already present in normal-appearing perilesional skin. Keratin fibres in the dermis are associated with clinical disease. Early lesions are characterized by neutrophilic abscess formation and influx of mainly histiocytes, and chronic lesions mainly by expansion of B cells and plasma cells in 'pseudo' follicles. Proliferating strands of follicular epithelium may initiate fistula formation. Mast cells are increased in all sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 21 publications
11
109
0
4
Order By: Relevance
“…A laphámrák kialakulására nagy valószínűséggel a HS-ben fennálló krónikus bőrgyulladás hajlamosít. Ezzel szemben a B-sejtes lymphomák emelkedett előfordulása rávilágít a limfociták és a termelt immunglobulinok szerepére (20), melyek előrehaladott esetekben válnak jellegzetessé és mutatnak malignus transzformációt.…”
Section: Epidemiológiai Tényezők Patológiai Relevanciávalunclassified
“…A laphámrák kialakulására nagy valószínűséggel a HS-ben fennálló krónikus bőrgyulladás hajlamosít. Ezzel szemben a B-sejtes lymphomák emelkedett előfordulása rávilágít a limfociták és a termelt immunglobulinok szerepére (20), melyek előrehaladott esetekben válnak jellegzetessé és mutatnak malignus transzformációt.…”
Section: Epidemiológiai Tényezők Patológiai Relevanciávalunclassified
“…Recently we demonstrated the presence of free keratin remnants in the dermis and in multinucleated giant cells and proposed that this is a key histological hallmark of HS [6]. We hypothesized that that these keratin remnants are derived from ruptured infundibular cysts and that HS is the result of an aberrant clearing/inflammation reaction of these remnants [6].…”
Section: Aberrant Immunological Response or Clearing Of Keratin Remnantsmentioning
confidence: 99%
“…We hypothesized that that these keratin remnants are derived from ruptured infundibular cysts and that HS is the result of an aberrant clearing/inflammation reaction of these remnants [6]. Moreover, it has been demonstrated that experimentally punctured dilated human hair follicles do form fistulas [43], which are a hallmark of severe HS.…”
Section: Aberrant Immunological Response or Clearing Of Keratin Remnantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a chronic disease with natural flare-ups and remissions, but in severe disease inflammation, pain and discharge are continuously present, resulting in a significantly compromised quality of life [2]. HS is probably the result of environmental factors in a genetically predisposed individual in which infundibular occlusion results in cyst formation, subsequent rupture and inflammation [3]. Putative risk factors include smoking, obesity and mechanical friction [1].…”
Section: Introductionmentioning
confidence: 99%